Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5603/kp.a2016.0057
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of troponin elevation by means of intracoronary electrocardiogram during percutaneous coronary intervention of coronary bifurcation lesions (from COronary SIde Branch Residual IschemiA and COllateralization Assessment Study; COSIBRIA & Co Study

Abstract: A b s t r a c t Background:The influence of periprocedural ischaemia on coronary artery bifurcation stenting (percutaneous coronary intervention [PCI]) remains uncertain. Aim:To determine the differences in rates of end procedural ischaemia after bifurcation lesion PCI detected with intracoronary electrocardiography (icECG).Methods: Unipolar icECGs were recorded before, during, and after stent placement and at the end of procedure in side branch (SB) and main branch (MB). Coronary wire was placed in all distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…The difference of the definitions that significant ST-segment changes on IC-ECG in each study was not very great. The reference standards reported in the diagnostic studies were varied, including FFR,5 13 echocardiogram14 and troponin 12 15 16…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The difference of the definitions that significant ST-segment changes on IC-ECG in each study was not very great. The reference standards reported in the diagnostic studies were varied, including FFR,5 13 echocardiogram14 and troponin 12 15 16…”
Section: Resultsmentioning
confidence: 99%
“…Vassilev et al found out that the exact size of recording electrode is the last 3 cm of every workhorse guidewire. 16 And Uetani found that the waveforms of IC-ECG were different in the same position between conventional uninsulated guidewires and polymer-covered wires. 11 However, we could not perform sensitivity analysis for different guide wires, limited by the included studies, to verify the hypothesis that different types of guide wires would affect the diagnostic accuracy of IC-ECG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations